1991
DOI: 10.1128/aem.57.9.2610-2616.1991
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of Giardia and Cryptosporidium spp. in surface water supplies

Abstract: Giardia and Cryptosporidium levels were determined by using a combined immunofluorescence test for source waters of 66 surface water treatment plants in 14 states and 1 Canadian province. The results showed that cysts and oocysts were widely dispersed in the aquatic environment. Giardia spp. were detected in 81% of the raw water samples. Cryptosporidium spp. were found in 87% of the raw water locations. Overall, Giardia or Cryptosporidium spp. were detected in 97% of the raw water samples. Higher cyst and oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
174
3
10

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(191 citation statements)
references
References 10 publications
4
174
3
10
Order By: Relevance
“…These results are in the range of values reported by LeChevallier and coworkers (i.e. 87%) [18] and by Roach and coworkers (i.e. 14%) [19].…”
Section: Occurrence Of Pathogens In River Water and Relationship Withsupporting
confidence: 85%
“…These results are in the range of values reported by LeChevallier and coworkers (i.e. 87%) [18] and by Roach and coworkers (i.e. 14%) [19].…”
Section: Occurrence Of Pathogens In River Water and Relationship Withsupporting
confidence: 85%
“…But, it is essential from a public health standpoint to determine whether oocysts are live or not. Viability is an important aspect in the detection of Cryptosporidium in environmental waters, as many oocysts are dead or damaged and thus do not pose a threat to public health (LeChevallier et al ., 1991). To determine more accurately the human health risk posed by C. parvum , we have developed an IMS-RT-PCR assay that discriminates between viable and non-viable C. parvum oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Giardia recoveries averaged 12% 2 18 using the USEPA method and 49% 2 91 using the Ongerth membrane method; Cryptosporidium recoveries averaged 8% 2 13 with the USEPA method and 9% 2 4 using the Ongerth membrane method. Other studies have reported higher recoveries (LeChevallier et al 1991(LeChevallier et al , 1995 but these recoveries are from seeded packed pellets which do not include the sampling and elution steps. The ICR method recoveries in this study were higher than previously reported (Clancy 1996) and may be due to sampling only a 10 l sample volume rather than the 100 l normally sampled.…”
Section: Discussionmentioning
confidence: 92%